Asset pricing under information with stochastic volatility - Bertram Düring (University of Konstanz, Center of Finance and Econometrics (CoFE), 2008)
Based on a general specification of the asset speci?c pricing kernel, we develop a pricing model using an information process with stochastic volatility. We derive analytical asset and option pricing formulas. The asset prices in this rational expectations model exhibit crash-like, strong downward movements. The resulting option pricing formula is consistent with the strong negative skewness and high levels of kurtosis observed in empirical studies. Furthermore, we determine credit spreads in a simple structural model.
urn:nbn:de:bsz:352-opus-116757
Keywords: 330; Pricing kernel; stochastic volatility; asset pricing; option pricing; credit spreads